Low-latency trading and price discovery: Evidence from the Tokyo Stock Exchange in the pre-opening and opening periods - Mario Bellia; Loriana Pelizzon; Marti G. Subrahmanyam; Jun Uno; Darya Yuferova (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2017)
We study whether the presence of low-latency traders (including high-frequency traders (HFTs)) in the pre-opening period contributes to market quality, defined by price discovery and liquidity provision, in the opening auction. We use a unique dataset from the Tokyo Stock Exchange (TSE) based on server-IDs and find that HFTs dynamically alter their presence in different stocks and on different days. In spite of the lack of immediate execution, about one quarter of HFTs participate in the pre-opening period, and contribute signifi- cantly to market quality in the pre-opening period, the opening auction that ensues and the continuous trading period. Their contribution is largely different from that of the other HFTs during the continuous period.
Keywords: G12; G14; 330; High-Frequency Traders (HFTs); Pre-Opening; Opening Call Auction; PriceDiscovery; Liquidity provision